(untitled) (Research, Society and Development, 2021)
The appearance of a new coronavirus, called SARS-CoV-2, started a COVID-19 pandemic, which resulted in more than 251 million infections with at least 5 million deaths associated with the disease, being reported by the WHO until November 2021. Objective: To describe the use of medicinal plants as a treatment for COVID-19 and the importance of the pharmacist in the state of Amazonas. Methods: This is descriptive-exploratory research, where data collection takes place virtually, seeking articles in scientific databases: Academic Google, SciELO, BVS, PubMed and Portal de Periódicos (CAPES). The research period of the articles comprised works published from 2015 to 2021 and the health descriptors used in the research were: Bioactive; COVID-19; Extracts; Medicinal Plants and Tea. For data collection and analysis, there was a process and flow to concentrate articles on the main research theme and to highlight the findings. Results: Regarding the disordered use of medicinal plants, most showed promising inhibitory activity related to viral infections in humans, but this does not mean that they are effective in combating coronavirus. It so happens that, like the tea from the bark of “quina quina”, other home remedies from food and medicinal plants were used to prevent or treat COVID-19, showing a cultural behavior, which sought to combat flu or flu symptoms caused by the disease. Final Considerations: The need to know and identify bioactive compounds, specific safe dose for formulations and potential drug-herb interactions before entering a clinical trial is known. In addition to the incessant search for new scientific evidence for therapeutic use, as well as the essential importance of the pharmacist regarding the use of herbal medicines during any endemic period in the search for new methods of patient care.